(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2020)
The paper highlights the contribution given by administrative law and jurisprudence to the debate around the right to have a child through heterologous fertilization, after the regulatory vacuum resulting from important judgments by the Italian Constitutional Court. This field represents an interesting test field for the role of public administration in protecting the choice to have a baby via heterologous fertilization, also paying due attention to financial issues and the rights of future generations.